2021
DOI: 10.1123/ijsnem.2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Dietary Nitrate on Exercise Tolerance, Muscle Oxygenation, and Cardiovascular Function in Patients With Peripheral Arterial Disease

Abstract: Previous studies have used supplements to increase dietary nitrate intake in clinical populations. Little is known about whether effects can also be induced through vegetable consumption. Therefore, the aim of this study was to assess the impact of dietary nitrate, through nitrate-rich vegetables (NRV) and beetroot juice (BRJ) supplementation, on plasma nitrate and nitrite concentrations, exercise tolerance, muscle oxygenation, and cardiovascular function in patients with peripheral arterial disease. In a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The lack of improvement in pain-free (claudication onset) or peak treadmill walk time in the present study was unexpected given previous individual reports showing improved walk test performance after acute ( 26 , 27 , 42 ) or chronic ( 25 ) inorganic nitrate supplementation in PAD patients. However, two additional supplementation studies, one using BR nitrate acutely ( 28 ) (70 mL Beet-IT) and one that administered sodium nitrite tablets for 3 months ( 43 ) reported no significant improvements in walk distances relative to placebo. When examined collectively in a recent meta-analysis of studies investigating dietary nitrate and other upregulators of NO in PAD ( 44 ), it was reported that the improvements in maximum walk distance/duration did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of improvement in pain-free (claudication onset) or peak treadmill walk time in the present study was unexpected given previous individual reports showing improved walk test performance after acute ( 26 , 27 , 42 ) or chronic ( 25 ) inorganic nitrate supplementation in PAD patients. However, two additional supplementation studies, one using BR nitrate acutely ( 28 ) (70 mL Beet-IT) and one that administered sodium nitrite tablets for 3 months ( 43 ) reported no significant improvements in walk distances relative to placebo. When examined collectively in a recent meta-analysis of studies investigating dietary nitrate and other upregulators of NO in PAD ( 44 ), it was reported that the improvements in maximum walk distance/duration did not achieve statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The dietary interventions tested were diverse and spanned the four different categories as described in Figure 1-NO donors in seven trials [31,45,47,55,58,62,65], antioxidants in nineteen trials [32][33][34][36][37][38][39][40][42][43][44]46,48,49,51,57,59,60,63], NOS inducers in four trials [50,53,61,66] and enhancers of NO availability in five trials (Table S1) [41,52,54,56,64]. Twenty-six RCTs had control groups that received a matched placebo that was identical in all aspects and nine used a non-identical placebo but otherwise similar management to the intervention group.…”
Section: Description Of Interventionsmentioning
confidence: 99%
“…Figure 4. Forest plot showing the effect of dietary supplements upregulating the NO pathway versus control on the maximum walking distance; studies stratified by risk of bias[33,34,36,37,39,43,45,47,[50][51][52][53][54][56][57][58]62,64].…”
mentioning
confidence: 99%
“…Most of the studies have been related to the health effects of beet consumption on people with cardiovascular disease who have reduced aerobic capacity, intolerance to exercise, and early onset of fatigue during physical activity and daily activities [86]. Avoort et al studied the effect of beet consumption before exercise in patients with arterial disease [87]. They showed that beets significantly delayed the onset of fatigue while walking on a treadmill.…”
Section: Use Of Two the Beets Exercise Interventions In Individuals W...mentioning
confidence: 99%
“…They showed that beets significantly delayed the onset of fatigue while walking on a treadmill. The mechanism of this process through the dilation of blood vessels and delivery of oxygen to active tissues have been mentioned [87]. Reddy et al [88] investigated the effect of beets on cancer cell growth and observed the inhibition of MCF-7 cell growth after the consumption of beets for 48 h. The anti-cancer properties of red beets have been investigated [66].…”
Section: Use Of Two the Beets Exercise Interventions In Individuals W...mentioning
confidence: 99%